Peran Lembaga Pendidikan dalam Pencegahan dan Penanggulangan Tindakan Kekerasan Pada Siswa - Apriadi Apriadi; Muammar Khadafie (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
The high number of child violence in Sumbawa regency in the last four years (2016-2019) shouldencourage the local government, the community and the educational institution to give special attention. Thedata issued byKPAIin 2018 showed that the child violence in school area increased significantly, particularlythe case of physical and sexual violence. The cases reached 51.20 %. Meanwhile, the regulation regardingthe prevention and tackling the violence in education unit has been determined through the regulation of theminister of education and culture of Indonesia Republic in 2015. The aim of this study is to understand therole of educational institutions in preventing and tackling the violence in educational environmentwith a casestudy in junior high school and senior high school across Sumbawa regency. The study used a qualitativedescriptive approach. This method focused on depth research in order to look at the role of educationalinstitution in preventing and tackling the violence in educational environment. The results of the study showedthat the educational institutions are less active to do a prevention and tackling the violence in the schoolenvironment. One of a routine active conducted by each school is ‘IMTAQ’(religious improvement). Besidesthat the kids’ friendly school and the fulfilment of the children’s right to create the kids’ friendly school hasnot fully understood by educational institutions in Sumbawa regency. Therefore, the kids’ friendly schoolcould not be implemented.